THE IMPACT OF NON-CASH SOCIAL ASSISTANCE THROUGH E-MONEY TO THE EXPANSION OF FINANCIAL INCLUSION IN ACEH - Amelyani, Nanda; Sjafruddin; Sufi; Iryani, Lisa; Alhakim, Indra; Muhayatsyah, Ali (J-ISCAN: Journal of Islamic Accounting Research, 2023)
Broad access to formal financing for poor households through the distribution of social assistance with electronic money (e-money) is believed to accelerate poverty alleviation. The distribution of social assistance through the non-cash system is a breakthrough made by the government to increase aid effectiveness and promote financial inclusion. Recent research has shown that some beneficiaries find it challenging to disburse aid with the system. They only use non-cash facilities to disburse aid and do not want to use the system for other financial services. This fact can be an obstacle to achieving financial inclusion. This study aims to investigate what factors influence beneficiaries' perceptions of using the cashless system. We surveyed one hundred and fifty non-cash beneficiaries in districts/cities in Aceh. The distribution of non-cash social assistance is expected to familiarize the community with saving, it turns out that it is only limited to the disbursement of social assistance, and the mechanism for saving is not immediately carried out by the beneficiaries. Financial inclusion in non-social assistance for the poor is a pseudo-financial inclusiveness and has no impact on poverty reduction.